1992
DOI: 10.1002/ar.1092330412
|View full text |Cite
|
Sign up to set email alerts
|

Follicle‐associated epithelium and medullary epithelial tissue of the bursa of Fabricius are two different compartments

Abstract: The bursae of Fabricius from the chicken and turkey were studied by light and electron microscopy and immunohistochemical methods. The study focused on the relationship of follicle-associated epithelium to the medulla. The follicle-associated epithelium was supported by 3 to 5 layers of stratified epithelial cells which were a continuation of the corticomedullary epithelial cells. The follicle-associated epithelium consisted of M cells and scattered secretory dendritic cells. The network of the reticular epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
8
37
0
Order By: Relevance
“…This epithelial line, whose basal lamina was continuous with that of the IFE, was positive to antikeratin (Viamontes et al, 1989;Olah and Glick, 1992) and anti-bursin antibodies (Viamontes et al 1989). During embryogenesis, the epithelial cells, together with the bud formation, expressed K1 antigen, and after hatching, this antigen was restricted to cortico-medullary and FAE cells (Olah et al, 2002).…”
Section: Cortico-medullary Epithelial Linementioning
confidence: 95%
See 4 more Smart Citations
“…This epithelial line, whose basal lamina was continuous with that of the IFE, was positive to antikeratin (Viamontes et al, 1989;Olah and Glick, 1992) and anti-bursin antibodies (Viamontes et al 1989). During embryogenesis, the epithelial cells, together with the bud formation, expressed K1 antigen, and after hatching, this antigen was restricted to cortico-medullary and FAE cells (Olah et al, 2002).…”
Section: Cortico-medullary Epithelial Linementioning
confidence: 95%
“…The IFE was reactive to anti-cytokeratin antibody (Viamontes et al, 1989;Olah and Glick, 1992).The basal layer lining the IFE contained bursin (Viamontes et al, 1989;Otsubo et al, 2001).The origin of FAE cells is controversial. It has been reported that the FAE cells are epithelial cells (Schaffner et al, 1974a;Schaffner et al, 1974b;Davenport and Allen, 1995;Paramithiotis and Ratcliffe, 1996), which are positive (Viamontes et al, 1989), or weakly positive (Olah and Glick, 1992) to anti-cytokeratin antibodies. Other authors reported that they are mesenchymal cells (Dolfi et al, 1981;Lupetti et al, 1983Lupetti et al, , 1986Lupetti et al, 1990), that are negative to anti-cytokeratin .…”
Section: Plical Epitheliummentioning
confidence: 99%
See 3 more Smart Citations